DEFERRED PAYMENT IN GOODS TRANSACTIONS WITH GOLD GUARANTEE (AN ISLAMIC LEGAL PERSPECTIVE) - Arifin, Neli (Universitas Muhammadiyah Surabaya, 2024)
This study aims to analyze deferred payment transactions in goods with a gold guarantee from the perspective of Islamic law. The research was conducted in Tebing Batu Village, Sebawi District, focusing on the understanding and practices of the community regarding such transactions. The research method employed was descriptive-analytical with a qualitative approach. Data were collected through observation, interviews, and documentary studies. The findings indicate that transactions involving deferred payment with a gold guarantee are a common practice in Tebing Batu Village. The community perceives it as an alternative allowing them to meet daily needs without immediate cash payment. However, there are diverse understandings and implementations related to Islamic legal aspects in these transactions. From the Islamic law perspective, transactions involving gold-backed deferred payments raise several considerations including principles of justice, freedom, and clarity in agreements. The study also explores scholars' views on the validity of such transactions according to Islamic jurisprudence. In conclusion, deferred payment transactions with a gold guarantee in Tebing Batu Village present complexities from the perspective of Islamic law. Therefore, a deep understanding and dialogue among the community, scholars, and government are necessary to ensure that these practices align with the values and principles of Islamic law cherished by the local community.